Wine of Cool-climate Areas in South Poland - Dobrowolska-Iwanek, J.; GÄ…stol, M.; Wanat, A.; KroÅ›niak, M.; Jancik, M.; Zagrodzki, P. (South African Journal of Enology and Viticulture, 2016)
A number of new vinery production regions, especially in the southern parts of Poland, have appeared in the last ten-odd years. This study was aimed at completing the chemical characterisation of wine produced from ten Polish grape cultivars planted near Krakow. The wine was analysed to determine organic acid concentrations, total polyphenols and extract content, antioxidant activity, alcohol content, total acidity and pH. Moreover, a sensory analysis was performed on the wine. Significant differences were recorded between red and white wine. The total acidity expressed as tartaric acid, and tartaric and malic acid concentrations, were significantly higher in white and red wines, whereas antioxidant activity and phenolic content were significantly higher in the red wines. Similarities and relationships between various parameters and specific wine brands were further examined with cluster analysis. Our results show that, under Polish climatic conditions, it is possible to produce wine with quality comparable to wine from established wine denomination regions. Selected wine brands showed high antioxidant activity (FRAP – ferric reducing antioxidant power) and a high level of polyphenols. This study also provides confirmation that wines from colder climates frequently reveal unique and desirable properties.